RESOLUTION OF CONSUMER DISPUTES THROUGH ARBITRATION BASED ON RULING NUMBER 038/ARBITRASE/2022/BPSK.MDN - Abdul Rahman Maulana Siregar; Rico Nur Ilham; Sardi; Sri Devi Zebua (CV. RADJA PUBLIKA, 2024)
Dispute problems often occur in the community and become legal problems and problems that need to be discussed from a juridical aspect, in order to find out the basis for a problem that arises due to indications that arise from misunderstanding, tolerance in the problem, resulting in confusion and the emergence of a problem. which was ultimately resolved through litigation and non-litigation efforts. Specifically regarding the discussion of dispute resolution efforts through non-litigation, in this case using the arbitration settlement method requires a resolution of consumer disputes through arbitration. The law provides an alternative way by providing non-litigation or out-of-court dispute resolution in the form of conciliation, mediation and arbitration. As part of alternative dispute resolution, consumer dispute resolution is resolved through the Consumer ispute Resolution Agency (BPSK) as in dispute Number 038/Arbitrase/2022/BPSK.Mdn. BPSK is an alternative solution in resolving consumer disputes regarding problems in society, although it does not escape peace efforts or legal resolution in judicial procedures.